ANALISIS KEUNTUNGAN PEDAGANG DAGING KELELAWAR DI PASAR TRADISIONAL KECAMATAN AMURANG DAN KECAMATAN MODOINDING KABUPATEN MINAHASA SELATAN - Kasenda, Defren Ch; Osak, R E.M.F; Lumy, T F.D; Oroh, F N.S (Universitas Sam Ratulangi, 2020)
PROFIT ANALYSIS OF THE BAT BUSHMEAT TRADER IN THE TRADITIONAL MARKET IN AMURANG AND MODOINDING DISTRICKS OF SOUTH MINAHASA REGENCY. This study aims to analyze how much profit bat traders make in traditional markets in South Minahasa Regency. This research was conducted using a survey method and analyzes the level of business profit and its ability to generate profit (profitability) in bat meat dealers in traditional markets in the South Minahasa Regency. The results of this study show that the total cost of bat dealers reached an average of IDR 3.800.068. with an average acceptance of bat traders of IDR 4.898.438 per week. The total profit per bat dealer per week was IDR 849,557. with a gross margin of the traditional Amurang market of 0.13 and the traditional Modoinding market of 0.29.